2021
DOI: 10.1002/jpen.2097
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐to‐lymphocyte ratio is associated with malnutrition risk estimated by the Royal Free Hospital–Nutritional Prioritizing Tool in hospitalized cirrhosis

Abstract: Background Liver cirrhosis is characterized by immune dysfunction, contributing to malnutrition. We previously revealed neutrophil‐to‐lymphocyte ratio (NLR) as an indicator of disordered immune system. Herein we aimed to (1) determine the optimal NLR cutoff that best predicts malnutrition risk and (2) clarify the association between NLR and nutrition status. Methods A total of 135 hospitalized patients with cirrhosis were included. Immune dysfunction was evaluated by levels of serum C‐reactive protein (CRP), N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…In contrast, SAT has been proved to uptake and deposit triglycerides, plasma FFAs, and responsible for producing leptin in charge of immune response and lipid metabolism (34)(35)(36). More recently, our results implicated that immune dysfunction measured by neutrophilto-lymphocyte ratio (NLR) is associated with malnutrition risk estimated by RFH-NPT in cirrhosis (5). Furthermore, the expression of circulating IL-6 and IL-8 was positively correlated with increased NLR values (37).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In contrast, SAT has been proved to uptake and deposit triglycerides, plasma FFAs, and responsible for producing leptin in charge of immune response and lipid metabolism (34)(35)(36). More recently, our results implicated that immune dysfunction measured by neutrophilto-lymphocyte ratio (NLR) is associated with malnutrition risk estimated by RFH-NPT in cirrhosis (5). Furthermore, the expression of circulating IL-6 and IL-8 was positively correlated with increased NLR values (37).…”
Section: Discussionmentioning
confidence: 68%
“…Notably, among eight screening tools for detecting the risk of malnutrition in cirrhosis, RFH-NPT represents the most accurate with a high sensitivity of 97.4% and a fair specificity of 73.3% ( 26 ). In addition, our previous work showed that malnourished status assessed by RFH-NPT is closely associated with immune dysfunction ( 5 ). Taken together, we preferentially adopt RFH-NPT in this work for identifying high risk of malnutrition in our retrospective cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RFH-NPT scores were calculated according to our previous depiction ( 16 ). Briefly, the risk of malnutrition was categorized into low (0 points), moderate (1 point), and high (2–7 points) in terms of RFH-NPT scores.…”
Section: Methodsmentioning
confidence: 99%
“…We and others have clarified that malnutrition is common in patients with cirrhosis and the necessity for performing nutritional screening among all subjects in the clinical practice [9][10][11]. In recent work, we used the Royal Free Hospital-Nutritional Prioritizing Tool (RFH-NPT) as an analytic metric, which is specifically designed and recommended for cirrhotics, and found that 53.3% of 135 patients are at high malnutrition risk [9,12]. Surprisingly, even if the deleterious influences of malnutrition related to cirrhosis are well known, the unified construct of malnutrition remains elusive in the literature.…”
Section: Introductionmentioning
confidence: 99%